Has the Polyploid Wave Ebbed? - Levin, Donald A. (Frontiers in Plant Science, 2020)
There was a wave of whole genome duplications during and subsequent to the K–Pg interface, which was followed by an increase in the proportion of species that were polyploid. I consider why this wave of polyploid speciation has continued to rise through the divergent evolution of polyploid lineages, and through rounds of homoploid and heteroploid chromosomal change. I also consider why the polyploid speciation wave is likely to rise in the next millennium. I propose that the speed of polyploid genesis through ploidal increase and through diversification among polyploids likely will be greater than the speed of diploid speciation. The increase in polyploid diversity has lagged well behind episodes of WGD, owing to the very long period required for species diversification either by lineage splitting or additional rounds of polyploidy, in addition to the long period of genomic adjustment to higher ploidal levels in neopolyploids.